Efficacy and Tolerability of Fitostimoline in Two Different Forms (Soaked Gauzes and Cream) and Citrizan Gel in the Topical Treatment of Second-Degree Superficial Cutaneous Burns - Patrizia Martini; Carlo Mazzatenta; Giorgio Saponati (Dermatology Research and Practice)
A total of 227 patients (mean age 41.3 years, 52% females) with at least one second-degree superficial cutaneous burn of thermal origin of a smallest transverse diameter ≥20 mm and a largest transverse diameter ≤90 mm were randomised to receive the topical application of aqueous extract of Triticum vulgare (Fitostimoline) in two different forms (soaked gauzes and cream) or catalase of horse origin in form of gel (Citrizan Gel), given up to healing or to a maximum of 20 days. The rate of lesion healing at end of study was significantly higher in patients treated with Fitostimoline (gauzes 97.3%, cream 91.5%) than in those receiving catalase (84.5%). The pooled Fitostimoline groups were also significantly more effective than catalase gel in reducing total symptoms score, pain at medication, pain at rest, and burning at end of study. Both formulations of Fitostimoline and catalase gel were well tolerated in terms of adverse effects in the site of application.